Ultrasound Diagnosis of Cholecystitis and Cholelithiasis: A Study of Various Types and Complications for Better Management (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Ultrasound examination plays a crucial role in diagnosing cholecystitis and cholelithiasis, but itsreliability in predicting inflammation severity and distinguishing between acute and chronic cholecystitis remainscontested. This study aimed to provide ultrasound examination of various types of cholecystitis and cholelithiasis.Materials and Methods: A total of 650 subjects, including 48 healthy controls and 602 patients who underwentsurgery for acute, chronic, destructive cholecystitis, or cholelithiasis, were examined using a Siemens scanner.Ultrasonography parameters assessed blood flow in the branches and veins of the cystic artery using color Dopplerscanning and pulsed-wave Doppler. Quantitative blood flow velocity indicators and angle-independent totalperipheral resistance indices were examined. Results: Gallbladder length and area were significantly increasedin acute, phlegmonous, and gangrenous inflammation compared to controls. Wall thickness exceeded 4–5 mmin acute and phlegmonous-gangrenous inflammation. Maximum systolic blood flow velocity in the cystic arterymore than doubled in acute, phlegmonous, and gangrenous inflammation, while minimum systolic velocityshowed no significant changes. Total peripheral resistance indices increased in chronic, phlegmonous, andgangrenous inflammation but remained within control values in acute inflammation. The control group showed nosignificant differences in ultrasonographic indicators across all age groups. Conclusion: These findings highlightthe importance of comprehensive clinical assessment alongside ultrasound imaging for accurate diagnosis andmanagement of cholecystitis and cholelithiasis.